Conservation of Arid Plants through Improved Understanding of Seed Biology as a Means of Enhancing the Functionality of Botanic Gardens - Nayyef, Alaa Shallal (Curtin University, 2018)
This study analysed the seed biology of species from the semi-arid Pilbara region to assist restoration programs. Afterripening, wet/dry cycling and scarification were found to overcome physiological dormancy in selected native understorey species, while seed priming was also found to enhance germination. Through a world-wide survey the study also defined the functionality of botanic gardens from different continents; the outcomes of which will aid the development of strategic planning for botanic gardens in arid regions.